Audit and Feedback Interventions for Antibiotic Prescribing in Primary Care: A Systematic Review and Meta-analysis - Xu, Alice X T; Brown, Kevin; Schwartz, Kevin L; Aghlmandi, Soheila; Alderson, Sarah; Brehaut, Jamie C; Brown, Benjamin C; Bucher, Heiner C; Clarkson, Janet; De Sutter, An; Francis, Nick A; Grimshaw, Jeremy; et al. (Clinical infectious diseases, 2025)
This systematic review evaluates the effect of audit and feedback (A&F) interventions targeting antibiotic prescribing in primary care and examines factors that may explain the variation in effectiveness. Randomized controlled trials (RCTs) involving A&F interventions targeting antibiotic prescribing in primary care were included in the systematic review. Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, CINAHL, and ClinicalTrials.gov were searched up to May 2024. Trial, participant, and intervention characteristics were extracted independently by 2 researchers. Random effects meta-analyses of trials that compared interventions with and without A&F were conducted for 4 outcomes: (1) total antibiotic prescribing volume; (2) unnecessary antibiotic initiation; (3) excessive prescription duration, and (4) broad-spectrum antibiotic selection. A stratified analysis was also performed based on study characteristics and A&F intervention design features for total antibiotic volume. A total of 56 RCTs fit the eligibility criteria and were included in the meta-analysis. A&F was associated with an 11% relative reduction in antibiotic prescribing volume (N = 21 studies, rate ratio [RR] = 0.89; 95% confidence interval [CI]: .84, .95; I2 = 97); 23% relative reduction in unnecessary antibiotic initiation (N = 16 studies, RR = 0.77; 95% CI: .68, .87; I2 = 72); 13% relative reduction in prolonged duration of antibiotic course (N = 4 studies, RR = 0.87 95% CI: .81, .94; I2 = 86); and 17% relative reduction in broad-spectrum antibiotic selection (N = 17 studies, RR = 0.83 95% CI: .75, .93; I2 = 96). A&F interventions reduce antibiotic prescribing in primary care. However, heterogeneity was substantial, outcome definitions were not standardized across the trials, and intervention fidelity was not consistently assessed. Clinical Trials Registration. Prospero (CRD42022298297).